Pengabdian Masyarakat: Pemberdayaan UMKM Melalui Pemasaran Digital dan Manajemen Keuangan di Bantimurung, Makassar - St Salmah Sharon; Yuyun Karysitin Meilisa Suade; Monalisa Monalisa; Erwin Erwin (PELITA NUSA TENGGARA, 2026)
This Community Service Program aims to empower micro, small, and medium enterprises (MSMEs) in the Bantimurung area of ​​Makassar by strengthening their digital marketing and financial management capacity to improve business sustainability. The main challenges faced by partners include low financial literacy, poor cash flow recording and management, and limited use of digital media in product marketing. This program is implemented using an educational and participatory approach combined with hands-on practice and mentoring. The implementation method includes preparation, digital marketing and financial management training, and mentoring and evaluation. The results of the activity indicate an increase in partners' understanding and skills in utilizing digital media as a means of promotion and expanding market reach, as well as increased awareness and ability of partners in simple financial recording, cash flow management, and separating business and personal finances. The high level of partner participation throughout the program reflects the program's relevance to the real needs of MSMEs. Overall, this program demonstrates that the integration of digital marketing and financial management, implemented in a contextual and applicable manner, can strengthen the competitiveness and resilience of MSMEs. The practical implications of this activity emphasize the importance of ongoing mentoring and collaboration between universities and the community in encouraging accountable, adaptive, and local economic sustainability-oriented MSME management.